Tantangan Strategi Tobacco Harm Reduction (THR) dalam Pembatasan Rokok Elektrik oleh Kaum Remaja - Nurul Hikmah Baharuddin; Andi Sani; Firman Firman; Nurhidayati Islamiah (FORIKES, 2023)
Tobacco control policies are one of the concerns in a series of sustainable development goals. In terms of reducing exposure to cigarette smoke or for smokers who cannot stop using tobacco products containing nicotine, electronic cigarettes or vapes are said to be a safer alternative to conventional cigarettes by prioritizing the concept of a